Cardioselective and cumulative oxidation of mitochondrial DNA following subchronic doxorubicin administration - Serrano, J. (1999)
We recently reported the preferential accumulation of 8-hydroxydeoxyguanosine (8OHdG) adducts in cardiac mitochondrial DNA (mtDNA) following acute intoxication of rats with doxorubicin (C.M. Palmeira et al., Biochim. Biophys. Acta, 1321 (1997) 101-106). The concentration of 8OHdG adducts decreased to control values within 2 weeks. Since conventional antineoplastic therapy entails repeated administration of small doses of doxorubicin, it was of interest to characterize the kinetics for the accumulation and repair of 8OHdG adducts in the various DNA fractions. Weekly injections of doxorubicin (2 mg/kg, i.p.) to adult male Sprague-Dawley rats caused a cumulative dose-dependent increase in the concentration of 8OHdG adducts in both mtDNA and nuclear DNA (nDNA) from heart and liver. Following six weekly injections, the concentration of 8OHdG in cardiac mtDNA was 50% higher than liver mtDNA and twice that of cardiac nDNA. In contrast to the rapid repair of 8OHdG observed during the first days following an acute intoxicating dose of doxorubicin, the concentration of 8OHdG adducts remained constant between 1 and 5 weeks following the last injection. This was true for all DNA fractions examined. The cardioselective accumulation and persistence of 8OHdG adducts to mtDNA is consistent with the implication of mitochondrial dysfunction in the cumulative and irreversible cardiotoxicity observed clinically in patients receiving doxorubicin cancer chemotherapy.